BUYUK IPAK YO’LINING MARKAZIY OSIYO SHAHARLARIDAGI TARAQQIYOT TUTGAN O’RNI - Hakimov Sherzod, Shotirov Latif (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the historical development of the Great Silk Road, its origins, geographical position, and its significance in trade. It explores how the cities and states surrounding the Silk Road benefitted from its presence and developed over time. The article also provides insights into various scholars' perspectives and their research on the Silk Road.